2013
DOI: 10.1093/treephys/tpt097
|View full text |Cite
|
Sign up to set email alerts
|

Condensed tannin biosynthesis and polymerization synergistically condition carbon use, defense, sink strength and growth in Populus

Abstract: The partitioning of carbon for growth, storage and constitutive chemical defenses is widely framed in terms of a hypothetical sink-source differential that varies with nutrient supply. According to this framework, phenolics accrual is passive and occurs in source leaves when normal sink growth is not sustainable due to a nutrient limitation. In assessing this framework, we present gene and metabolite evidence that condensed tannin (CT) accrual is strongest in sink leaves and sequesters carbon in a way that imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The benefits of CTs have been demonstrated in only support the primary plant metabolism (Haslam, 1981). It is now well established that CT synthesis is under genetic control (Szczyglowski and Stougaard, 2008;Scioneaux et al, 2011;Cheynier et al, 2013;Escaray et al, 2014) and that expression depends on the plant species and plant parts (Larkin et al, 1997;Gebrehiwot et al, 2002;Abeynayake et al, 2012;Ferreyra et al, 2012;Hancock et al, 2012;Verdier et al, 2012;Cheynier et al, 2013;Harding et al, 2013;Mouradov and Spangenberg, 2014;Pérez-Díaz et al, 2014;Zhou et al, 2015;Zhu et al, 2015;Chezem and Clay, 2016).…”
Section: Roles Of Tannins In Plants and Challenges To Harnessing Theimentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of CTs have been demonstrated in only support the primary plant metabolism (Haslam, 1981). It is now well established that CT synthesis is under genetic control (Szczyglowski and Stougaard, 2008;Scioneaux et al, 2011;Cheynier et al, 2013;Escaray et al, 2014) and that expression depends on the plant species and plant parts (Larkin et al, 1997;Gebrehiwot et al, 2002;Abeynayake et al, 2012;Ferreyra et al, 2012;Hancock et al, 2012;Verdier et al, 2012;Cheynier et al, 2013;Harding et al, 2013;Mouradov and Spangenberg, 2014;Pérez-Díaz et al, 2014;Zhou et al, 2015;Zhu et al, 2015;Chezem and Clay, 2016).…”
Section: Roles Of Tannins In Plants and Challenges To Harnessing Theimentioning
confidence: 99%
“…All enzymes involved in the biosynthesis of the CT building blocks (i.e., flavan-3-ols) have been identified, apart from the elusive final condensing enzyme(s) (Harding et al, 2013). Two genes and several myeloblastosis (MYB) transcription factors (i.e., proteins with myeloblastosis DNAbinding domains that regulate CT synthesis) are responsible for the production of two of the flavan-3-ols (i.e., catechin and epicatechin; Ferreyra et al, 2012;Cheynier et al, 2013;Zhu et al, 2015;Chezem and Clay, 2016), but the genes and transcription factors for the other flavan-3-ols await identification.…”
Section: Tannin Variation In Germplasm Collections and Potential For mentioning
confidence: 99%
“…Secondary metabolism was not altered in RNAi compared to WT plants278 Non-structural phenylpropanoid end-products, including flavonoid-derived proanthocyanidins, or condensed tannins (CT), and phenolic glycoside salicinoids typically accumulate in leaves and 280 bark of poplars and other species of the family Salicaceae(Harding et al 2005;Harding et al 2014). They comprise important metabolic sinks because of their abundance, metabolic 282 stability and impact on trophic interactions(Kleiner et al 1999;Ruuhola and Julkunen-Tiitto 2000;Kandil et al 2004).…”
mentioning
confidence: 99%
“…Leaf CTs of natural aspen populations are strongly tied to genotype (Lindroth et al, 2011;Robinson et al, 2012;Bandau et al, 2015;Decker et al, 2016), a feature that was also observed in our transformed genotypes. CTs are considered to be antioxidant phenolic polymers (Gourlay and Constable, 2019) that are expected to influence the presence and impact of plantconsuming microorganisms and herbivores (Mutikainen et al, 2000;Bailey et al, 2005;Barbehenn and Constabel, 2011), although they also express a high degree of plasticity in response to environmental factors such as nitrogen addition (Bandau et al, 2015) and they may be equally important and indicative of the extent of internal recovery and the mode of growth (Harding et al, 2013;Lindroth and Madritch, 2015;Decker et al, 2016). However, the two lines in this experiment that suffered from elevated chewing symptoms varied in tannin content, with 35S:HjAXE giving lower and 35SAnAXE1 higher foliar CT concentrations when compared to WT (Figures 5B,C).…”
Section: Variability In Foliar Phenolics and Resistance Properties Ofmentioning
confidence: 99%